UltraViolet - Wimmer, Kurt, 1964-; Jovovich, Milla; Bright, Cameron, 1993-; Chinlund, Nick, 1961-; Fichtner, William; Wong Ngok Tai, Arthur; Badelt, Klaus; Sony Pictures Home Entertainment (Firm) (Culver City, Calif. : Sony Pictures Home Entertainment, 2006)
Human society has been decimated by a holocaust caused by biological warfare research gone wrong. The intent was to create super-soldiers, but a genetically-engineered virus turns infected humans into Hemophages. These human, vampire-like sub-species have enhanced physical abilities. In the infection-paranoid and technologically advanced society that follows, Violet is a singular Hemophage warrior battling the totalitarian dictator who is determined to wipe out her species at any cost.
Title from container.
Special features: "UV protection": the making of 'UltraViolet'; commentary with Milla Jovoch; never before seen bonus footage.
Director of photography, Arthur Wong Ngok Tai ; editor, William Yeh ; music, Klaus Badelt ; costume designer, Joseph Porro ; production designer, Choo Sung Pong.
Milla Jovovich, Cameron Bright, Nick Chinlund, William Fichtner.
Unrated.
DVD, region 1; widescreen presentation; Dolby Digital.
Keywords: Biological warfare -- Drama; Mutation (Biology) -- Drama; Totalitarianism -- Drama; Feature films; Thrillers (Motion pictures); Thrillers (Television programs); Video recordings for the hearing impaired; Thriller -- Feature; Suspense films; Science fiction films; Fantasy films